The Politeness Strategies used by the Students with Regional Multicultural Background (Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
his study aimed to describe the politeness strategy used by the students of Language and Science Faculty in Wijaya Kusuma Surabaya University with different regional multicultural backgrounds. The data in this qualitative study were taken from 20 participants, in which 10 participants were non-Javanese, and 10 participants were Javanese. The data were collected, documented, transcribed, reduced, and coded to make the analysis easier. The analysis was done by following these procedures 1) the data were classified based on the students’ place of origin, types of politeness, and the strategies they used and displayed 2) the data were analyzed using Brown’s and Levinson’s theory of politeness strategies. The finding reveals that both groups of students used negative and positive politeness strategies; however, the types of strategies are different. The non-Javanese students used strategies of apologizing and being pessimistic in negative politeness strategy while the Javanese students used strategies of apologizing, hedging, and giving deference. In positive politeness strategies, the non-Javanese students used strategies of avoiding disagreement, promising, exaggerating, and seeking agreement; meanwhile, the Javanese students used avoiding disagreement, exaggerating, and giving for reason strategies.